Efficient ECH-assisted plasma start-up using trapped particle configuration in the versatile experiment spherical torus. (3rd October 2016) - An, YoungHwa; Lee, Jeongwon; Jo, JongGab; Jung, Bong-Ki; Lee, HyunYeong; Chung, Kyoung-Jae; Na, Yong-Su; Hahm, T.S.; Hwang, Y.S.
Abstract: An efficient and robust ECH (electron cyclotron heating)-assisted plasma start-up scheme with a low loop voltage and low volt-second consumption utilizing the trapped particle configuration (TPC) has been developed in the versatile experiment spherical torus (VEST). The TPC is a mirror-like magnetic field configuration providing a vertical magnetic field in the same direction as the equilibrium field. It significantly enhances ECH pre-ionization with enhanced particle confinement due to its mirror effect, and intrinsically provides an equilibrium field with a stable decay index enabling prompt plasma current initiation. Consequently, the formation of TPC before the onset of the loop voltage allows the plasma to start up with a lower loop voltage and lower volt-second consumption as well as a wider operation range in terms of ECH pre-ionization power and H2 filling pressure. The TPC can improve the widely-used field null configuration significantly for more efficient start-up when ECH pre-ionization is used. This can then be utilized in superconducting tokamaks requiring a low loop voltage start-up, such as ITER, or in spherical tori with limited volt-seconds. The TPC can be particularly useful in superconducting tokamaks with a limited current slew-rate of superconducting PF coils, as it can save volt-second consumption before plasma current initiation by providing prompt initiation with an intrinsic stable equilibrium field.